Penetapan Model Pengelolaan Limbah Cair Tempe di Plaju Ulu dengan Metode Interpretive Structural Modeling - Destri, Erin; Rejo, Amin; Hanum, Laila (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Destri, E., Rejo, A., Hanum, L. (2024). Determination of tempeh wastewater management model in plaju ulu with interpretive structural modeling method. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembangg 21 Oktober 2024. (pp. 409–425). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The development of the household-scale tempeh industry in Plaju Ulu, Palembang, produces wastewater that has the potential to disrupt environmental balance if not managed properly. This research aimed to establish appropriate recommendations for a model of wastewater management for tempeh to minimize the impacts caused by waste disposal. This study uses the Interpretive Structural Modeling (ISM) approach to determine the relationships between elements in formulating the model recommendations. The framework variables for this research include three main elements: the background conditions of education, economy, and socio-cultural aspects of tempeh producers. The research findings indicate that the implementation of wastewater management for tempeh in Plaju Ulu needs to be supported by strengthening formal education through workshops or seminars for tempeh producers on effective waste management techniques, or by collaborating with academics to develop innovative waste processing technologies. The success of waste management also relies on the welfare of tempeh producers, necessitating efforts such as product diversification from wastewater raw materials and providing access to product certification to enhance competitiveness and sales. Additionally, the management of tempeh liquid waste requires the development of local regulations governing the disposal and management of wastewater, involving tempeh associations in discussions to ensure that the management stages are accepted and implemented effectively. A model for managing tempeh wastewater that focuses on education, economy, and socio-cultural aspects is expected to create a sustainable environmental system through good collaboration among all partiesn.